Long-term Soft Contact Lens use and Dry Eye Symptoms in Panca Budi Development University Students - Siregar, Okkis Razuansyah; Azrial, T. Indra (Hasanuddin Medan, 2023)
Contact lenses are usually attached to the cornea of the eye contact lenses usually have a corrective purpose like glasses but the difference is that contact lenses are lighter and almost invisible. Dry eye caused by contact lenses is one of the health problems is developing in the community, one of the reasons and ultimately has an impact on vision problems where eventually vision becomes blurry. The purpose of this study was to ascertain how contact lenses affected dry eyes. This study used a quantity method for its survey investigation. DTA collecting methods use a nominal scale questionnaire. Using a straightforward linear regression test, the study sample consisted of 49 respondents who are students at the University Pembangunan Panca Budi Medan Faculties Agama Islam Dan Humaniora. It was determined from the results that there is no significant correlation between the dependent variable, namely dry eye symptoms, and the independent variable, the length of time using soft contact lenses. The R square values indicate that there is only a 19,8% correlation between the symptoms of dry eyes and long-term contact lens usage.